Conversion of poultry-fat waste to a sustainable feedstock for biodiesel production via microbubble injection of reagent vapor. (15th August 2021) - Javed, Fahed; Shamair, Zufishan; Hafeez, Ainy; Fazal, Tahir; Aslam, Rabya; Akram, Sarfaraz; Rashid, Naim; Zimmerman, William B.; Rehman, Fahad
Abstract: Sustainability and the price of feedstock are the key parameters governing the economics of biodiesel production. Higher price of biodiesel is the major obstacle in its commercialization. Chicken fats, otherwise a waste and environmental nuisance, are an attractive feedstock for cleaner biodiesel production because of low cost and worldwide availability. Moreover, Establishment of thermodynamic equilibrium in esterification reaction limits the overall conversion and reduces the rate of reaction. A new vapor (methanol bubble)-liquid contacting method has been proposed to analyze the hypothesis that bubble reactor can "push" the biodiesel production near completion. Simultaneous removal of water from the system would "pull" the equilibrium in the forward direction. Kinetic investigation shows that the reaction occurs, indeed, at the vapor-liquid interface and consequently yielding a higher conversion of 89.90% in 30 min – significantly higher than any previously reported studies for chicken fat based biodiesel. Furthermore, the use of, an economical and already used at commercial grade catalyst, p-Toluene sulfonic acid eliminates the need to produce a catalyst at commercial scale before it could be used in an industrial process. These factors make microbubble mediated biodiesel production from chicken fat oil using p-Toluene sulfonic acid a lucrative option. Graphical abstract: Image 1